Regulation of Criminal Acts of Sexual Violence in Indonesia from the Perspective of CEDAW: Protection of Women's Human Rights - Wiarti, July; Udasmoro, Wening; Supriyadi (As-Siyasi: Journal of Constitutional Law, 2025)
As a State Party to the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), Indonesia is legally obliged to adopt effective legislative measures to eliminate discrimination against women, including sexual violence. Despite this commitment, sexual violence remains prevalent, raising concerns regarding the adequacy of the existing legal framework. This study aims to re-examine Indonesia’s sexual violence regulations in light of CEDAW obligations and Feminist Legal Theory (FLT), particularly regarding their capacity to recognize and protect women’s lived experiences. The research employs normative legal research, analyzing secondary legal materials through conceptual and comparative approaches to legislation. The findings demonstrate that Indonesia’s regulatory framework on sexual violence remains fragmented and uneven. While the Criminal Code narrowly constrains the definition of sexual violence, the Criminal Procedure Code fails to adequately address women’s rights and gender-sensitive victim protection. Revisions to the Child Protection Law have strengthened prohibitions against sexual violence but remain limited in scope and apply exclusively to child victims. The Domestic Violence Law criminalizes sexual violence within the household context, yet its protection is confined to forced sexual intercourse and does not fully capture broader forms of sexual abuse. Conversely, the Women’s Empowerment and Child Protection Law represents a significant normative advancement, providing a more comprehensive prohibition of sexual violence and stronger guarantees for women’s rights. This study contributes to feminist legal scholarship by highlighting the persistence of gender-biased legal constructions and underscores the need for a coherent, victim-centered, and CEDAW-compliant legal framework to effectively address sexual violence in Indonesia